PENGARUH INDEPENDENSI DEWAN KOMISARIS, UKURAN PERUSAHAAN, DAN PELUANG PERTUMBUHAN TERHADAP PRUDENSI AKUNTANSI (Studi Empiris Pada Perusahaan Sektor Teknologi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020–2023) - Swissia, Pebrina; Irawati, Anik; Yaumil (Jurnal Bisnis Darmajaya, 2026)
This study aims to examine the effect of board of commissioners’ independence, company size, and growth opportunity on accounting prudence in technology sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period. The data used are secondary data obtained from companies’ annual reports. The sampling technique used purposive sampling, resulting in 12 companies with a total of 48 observations. The analysis method employed is multiple linear regression using IBM SPSS version 25. The results show that simultaneously all variables have a significant effect on accounting prudence. Partially, board independence, company size, and growth opportunity have a positive and significant effect on accounting prudence. This indicates that higher board independence, larger company size, and greater growth opportunities lead to a higher level of prudence in financial reporting. This study implies that accounting prudence is influenced by corporate governance, firm characteristics, and growth opportunities